2008
DOI: 10.1093/cvr/cvn222
|View full text |Cite
|
Sign up to set email alerts
|

Central infusion of aldosterone synthase inhibitor attenuates left ventricular dysfunction and remodelling in rats after myocardial infarction

Abstract: These data suggest that aldosterone produced locally in the brain acts as the main agonist of mineralocorticoid receptors in the CNS and contributes substantially to the progressive heart failure post MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…Together, these findings indicate that ICV FAD286, indeed, causes specific blockade of the aldosterone synthase enzyme in the CNS. Similar to our previous studies in Wistar rats (21,22), ICV FAD286 did not decrease hypothalamic aldosterone to levels lower than in rats with regular salt intake. These findings may indicate the presence of two pools of aldosterone in the hypothalamus, one locally produced in the brain and one reflecting uptake from the circulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Together, these findings indicate that ICV FAD286, indeed, causes specific blockade of the aldosterone synthase enzyme in the CNS. Similar to our previous studies in Wistar rats (21,22), ICV FAD286 did not decrease hypothalamic aldosterone to levels lower than in rats with regular salt intake. These findings may indicate the presence of two pools of aldosterone in the hypothalamus, one locally produced in the brain and one reflecting uptake from the circulation.…”
Section: Discussionsupporting
confidence: 91%
“…The doses of FAD286 were initially extrapolated from studies using oral FAD286 (8,25). ICV infusion of FAD286 at a rate of 100 g ⅐ kg Ϫ1 ⅐ day Ϫ1 showed marked inhibitory responses in rats with ICV infusion of Na ϩ -rich aCSF (21) and in rats after myocardial infarction (22). The ICV dose of spironolactone was adopted from previous studies (9,23) and is markedly lower than orally active doses (23).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In a previous study, Connell et al 1 showed that the central nervous system can produce aldosterone. Furthermore, using FAD286, Gomez-Sanchez et al 2 and Hung et al 6,7 proved that aldosterone is synthesized in the brain. Kumar et al 4 demonstrated the presence of aldosterone-related mRNA species in the RVLM.…”
Section: Effect Of Fad286 On Bulbospinal Neurons In the Rvlmmentioning
confidence: 99%
“…4 Furthermore, aldosterone is involved in remodeling after myocardial infarction, and central blockade of aldosterone has been shown to attenuate cardiac remodeling. 5,6 Recent studies have demonstrated the existence of an aldosterone system in the brain, 4 and an increase in [Na þ ] in cerebrospinal fluid (CSF) has been shown to increase aldosterone biosynthesis. 7 Although the mechanism was unknown, Zhang et al 3 demonstrated that aldosterone upregulated key elements (angiotensin II type 1 receptor and angiotensin-converting enzyme in the brain reninangiotensin system) and induced oxidative stress in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation